ANALYSIS OF THE DISTRIBUTION OF THE EVENT OF DENTAL FEVER THROUGH THE APPLICATION OF GEOGRAPHIC INFORMATION SYSTEM DATA - Lintje Boekosoe (Universitas Negeri Gorontalo, 2021)
Every year dengue hemorrhagic fever (DHF) is still a public health problem, especially in Gorontalo City. Monitoring activities for patients need to be carried out to prevent disease transmission caused by mosquito bites as an intermediary vector. The utilization of Geographic Information Systems (GIS) related to the monitoring and identifying DHF mosquitoes has recently been widely used in public health science. This study aims to describe the pattern of the spread of dengue fever events through the application of geographic information system data in surveillance activities. This research is a descriptive-analytic study with an ecological approach and geographic information; the design used is Time Series. The research was conducted over six months. The study results based on the results of the Spearmen correlation test between climatic conditions and the incidence of DHF obtained a significance value of p 0.05. The distribution pattern of dengue fever in Gorontalo City is not related to climatic factors (temperature, humidity, rainfall, and rainy days). Conclusion: The distribution pattern of dengue fever in Gorontalo City is not related to climatic factors, including temperature, humidity, rainfall, and rainy days.